THE IMPORTANCE OF DEVELOPING CHILDREN’S CREATIVE THINKING THROUGH INSTRUMENTS IN MUSIC LESSONS (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the issues of developing children's creative thinking through the use of musical instruments in music lessons from a scientific and pedagogical perspective. The educational, aesthetic and creative significance of music lessons organized on the basis of the rich musical heritage of the Uzbek people is highlighted. The possibilities of developing students' musical perception, independent thinking and creative abilities with the help of musical instruments are revealed. Also, the forms of organizing music lessons and their pedagogical effectiveness are substantiated.
Keywords: Music education, musical instruments, creative thinking, aesthetic education, musical perception, Uzbek musical culture, music pedagogy, children's creativity.